Inequitable Chronic Lead Exposure: A Dual Legacy of Social and Environmental Injustice. Issue 3 (July 2016) - Leech, Tamara G. J.; Adams, Elizabeth A.; Weathers, Tess D.; Staten, Lisa K.; Filippelli, Gabriel M.
Abstract : Both historic and contemporary factors contribute to the current unequal distribution of lead in urban environments and the disproportionate impact lead exposure has on the health and well-being of low-income minority communities. We consider the enduring impact of lead through the lens of environmental justice, taking into account well-documented geographic concentrations of lead, legacy sources that produce chronic exposures, and intergenerational transfers of risk. We discuss the most promising type of public health action to address inequitable lead exposure and uptake: primordial prevention efforts that address the most fundamental causes of diseases by intervening in structural and systemic inequalities.